Participatory Water Quality Monitoring System for the Gajahwong River, Yogyakarta City, Indonesia - Sulistiyowati, Eka; Uyun, Shofwatul (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
This paper presents the development of Suka Peta (an integrated web-based system of participatory water quality monitoring), which has been developed by the researcher team of the State Islamic University Sunan Kalijaga, Yogyakarta, Indonesia. The system is designed to collect various types of data to generate a report on the water quality status of a river. The study followed a method for research and development that includes the design, development, implementation, and evaluation stages. The final product of this research is a web-based application that could be accessed publicly through www.status-sungai.com. During the evaluation stage, we conducted an FGD with stakeholders in the Gajahwong River community. The result confirmed that the application has a high potential for engaging the community in water quality monitoring. In addition, the participants have been able to use the application and participate in water quality monitoring efforts.